Anisotropy of pore size classes’ connectivity related to soil structure under no tillage - Lozano, Luis Alberto (2013)
No-tillage (NT) systems have been increasing during the last several decades. Development of a near-surface layer of laminar structure under NT has also been reported. The objectives of this work were to determine whether preferential connectivity of different pore size classes in two differently textured soils under NT exists and to propose a new index of pore connectivity based on water flux (Cw). The study was carried out at two sites in the Pampas Region of Argentina under long-term NT. Site 1 had a loamy A-horizon, and Site 2 had a sandy loam A-horizon. Undisturbed samples were extracted in vertical and horizontal directions within the first 8 cm of the soil. Saturated hydraulic conductivity (K s), near-saturated hydraulic conductivity (h: −50, −100, −200, −300, and −500 cm), pore size distribution from water retention curve, and total porosity were determined. The index of pore connectivity based on water flux, Cw, was developed as a ratio between K and pore volume for each pore size class. Site 1 showed laminar structure in the A-horizon, whereas Site 2 showed a blocky structure. We found a preferential connectivity in horizontal direction of macropores in Site 1. The index of pore connectivity was useful to assess the presence of preferential orientation of different pore size classes. In future studies, the connectivity of the different pore size classes should not be neglected.